Disección coronaria espontánea posterior a ejercicio: presentación de un caso y revisión bibliográfica - Ugalde P., Héctor; Cecilia Yubini, María; Sanhueza, Maria Ignacia; Rozas, Sebastián; Dussaillant N., Gastón (Revista Hospital Clínico Universidad de Chile, 2013)
Spontaneous coronary dissection (SCD) is a rare cause of acute coronary syndrome (ACS) in patients with no risk factors, usually described in young women within delivery period. The test of choice to approach diagnosis is coronary angiography, which could result therapeutic as it achieves myocardial revascularization though angioplasty. Occasionally, complementary radiologic techniques are required for diagnosis, as well as other treatments such as coronary bypass surgery (CBS). The prognosis of successfully revascularized patients is favorable, generally with no recurrence. We report the case of a 25 year-old woman, with no medical records, who experienced two episodes of ACS; first after exercise and two days later while she was at rest,revascularized in our hospital due to a double SCD that required CBS with a propitious evolution and remaining asymptomatic trough a six-year follow up.